Search computing broadening web search - Ceri, Stefano,d1955-; Brambilla, Marco,d1976- (Lecture notes in computer science, 2012)
This volume in the Search Computing series offers 16 timely papers on search computing problems and issues, arranged in four sections: extraction and integration; query and visualization paradigms; exploring linked data and games, social search and economics.